2016
DOI: 10.3847/0004-637x/823/2/151
|View full text |Cite
|
Sign up to set email alerts
|

Protostar L1455 Irs1: A Rotating Disk Connecting to a Filamentary Network

Abstract: We conducted IRAM-30 m C 18 O (2-1) and SMA 1.3 mm continuum 12 CO (2-1) and C 18 O (2-1) observations toward the Class 0/I protostar L1455 IRS1 in Perseus. The IRAM-30 m C 18 O results show IRS1 in a dense 0.05 pc core with a mass of 0.54 M e , connecting to a filamentary structure. Inside the dense core, compact components of 350 au and 1500 au are detected in the SMA 1.3 mm continuum and C 18 O, with a velocity gradient in the latter one perpendicular to a bipolar outflow in 12 CO, likely tracing a rotation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…The two Class 0 protostars IRAS16253 and IRAS15398 have been observed with ALMA by Yen et al (2017), who found a candidate disk radius of 20 au in IRAS15398 and an upper-limit disk radius of 6 au in IRAS16253. The Class 0 L1455 IRS1 was observed with the SMA, and the size of its protostellar disk was constrained to < 200 AU (Chou et al 2016). The HH211 Class 0 protostar was observed with ALMA, and its disk radius was constrained to < ∼ 10 au .…”
Section: Comparison With Other Workmentioning
confidence: 99%
“…The two Class 0 protostars IRAS16253 and IRAS15398 have been observed with ALMA by Yen et al (2017), who found a candidate disk radius of 20 au in IRAS15398 and an upper-limit disk radius of 6 au in IRAS16253. The Class 0 L1455 IRS1 was observed with the SMA, and the size of its protostellar disk was constrained to < 200 AU (Chou et al 2016). The HH211 Class 0 protostar was observed with ALMA, and its disk radius was constrained to < ∼ 10 au .…”
Section: Comparison With Other Workmentioning
confidence: 99%
“…With recent interferometric observations at (sub-)millimeter wavelengths, Keplerian disks with radii of tens to hundreds of au have been detected around several embedded Class 0 and I protostars (Lommen et al 2008;Takakuwa et al 2012;Tobin et al 2012;Brinch & Jørgensen 2013;Murillo et al 2013;Ohashi et al 2014;Chou et al 2014;Harsono et al 2014;Lindberg et al 2014;Lee et al 2014Lee et al , 2016Yen et al 2014Yen et al , 2017Aso et al 2015;Chou et al 2016). On the other hand, there is a group of Class 0 protostars with envelope rotations on a 1000 au scale that are one order of magnitude slower than other Class 0 protostars (Brinch et al 2009;Yen et al 2010Yen et al , 2015aMaret et al 2014), and they do not exhibit Keplerian disks with sizes larger than 10-20 au (Maury et al 2010;Oya et al 2014;Yen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This protostar is one of the brightest Class I sources in the L1455 region with a bolometric luminosity of 3.6 L (Dunham et al 2013). Goldsmith et al (1984) and Chou et al (2016) showed that the source is associated with a Keplerian disk (r < 200 au) and drives an high velocity outflow mapped in CO and C 18 O out to distances of ∼ 6000 au. This source is also associated with three knots detected in H 2 lines at near-infrared wavelengths (Davis et al 1997), which are located symmetrically with respect to the driving source in agreement with the collimated outflow structure imaged by Curtis et al (2010).…”
Section: L1455-irs1mentioning
confidence: 93%